Mindful Parenting, Kemandirian dan Perkembangan Motorik Anak Down Syndrome: Analisis Bibliometrik - Gusyuja Fauzi Adha; Jajat; Finaldhi Palgunadhi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the development of scientific publications on mindful parenting, independence, and motor development in children with Down syndrome using a bibliometric approach. The study employed a bibliometric method based on data retrieved from the Scopus database covering the period from 2017 to 2026. The data were analyzed using VOSviewer software to identify (1) publication trends, (2) the most highly cited articles, (3) the most productive authors and countries, and (4) the co-occurrence of keywords. The results revealed a steady increase in the number of publications, rising from 21 articles in 2017 to a peak of 95 articles in 2025. The United States was the most productive country, contributing 132 documents with a total of 2,285 citations, while Helena Moreira was identified as the most productive author with 20 publications and 627 citations. Keyword co-occurrence analysis indicated that the existing literature is predominantly focused on mindfulness, parenting stress, mental health, and parent–child relationships. In contrast, studies specifically examining the relationship between mindful parenting, independence, and motor development in children with Down syndrome remain relatively limited. In conclusion, this bibliometric analysis highlights substantial opportunities for future research to explore the role of mindful parenting in promoting independence and enhancing motor development among children with Down syndrome. Keywords: Bibliometric Analysis, Down Syndrome, Independence, Mindful Parenting, Motor Development